High-temperature Oxidation of Fe-Cr Steels in Steam Condition – A Review - Tedi Kurniawan; Farah Alia Binti Fauzi; Yuli Panca Asmara (Universitas Pendidikan Indonesia, 2016)
The development of supercritical (SC) and ultra-supercritical (USC) power plants requires materials with better corrosion properties. Deep understanding on the oxidation mechanism in the boiler environment is one of the important factors to support this development. In this work, high temperature oxidation of Fe-Cr steels in steam condition is reviewed. Several mechanisms that explain the effect of water vapor in the oxidation behavior the steel were presented.